Systematic Review: The Effect of Celery on Blood Pressure in Menopause - Niken Bayu Argaheni (Journal of Ners and Midwifery, 2022)
Menopause in women associated with depletion of follicles ovaries accompanied by physical and psychological changes. Common comorbidity experienced by menopausal women is hypertension. The purpose of this research was to find out the effect of celery on blood pressure in menopause. The systematic review used database from: Google Scholar. The search results that meet the criteria are then analyzed for articles. Celery (Apium graveolens L.) is one of the types of herbal therapy to treat hypertension in menopause. The simple use of celery was by boiled water which was considered safe for menopausal women to consume. This intervention could be applied as an alternative theraphy in treating menopausal woman in hypertension.